2016
DOI: 10.1111/1471-0528.14413
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive method preferences and provision after termination of pregnancy: a population‐based analysis of women obtaining care with the British Pregnancy Advisory Service

Abstract: Objective To examine contraceptive choices among women seeking termination of pregnancy (TOP) and the provision of the chosen methods. Design Population-based study. Setting British Pregnancy Advisory Service (BPAS) clinics in England and Wales. Population Between 1 January 2011 and 31 December 2014, 211 215 women had a TOP at BPAS, were offered contraceptive counselling, and were eligible to obtain contraception at no cost. Methods We examined electronic records from BPAS and assessed the proportions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…At a minimum, women should be made aware of the imminent return of their fertility and of the contraceptive methods available on the day of abortion. Many women find contraceptive counseling in the abortion setting acceptable: In a large, populationbased study of 211,215 women receiving surgical and medical abortion in the United Kingdom, 85% of women accepted contraceptive counseling, which followed a shared decision-making approach, and most of these women then chose to receive a method of contraception from the clinic [18]. In the general population, high-quality interpersonal communication may influence uptake of highly effective contraceptives and continuation of those methods at 6 months [19,20].…”
Section: How Should Contraceptive Counseling Be Performed At the Timementioning
confidence: 99%
“…At a minimum, women should be made aware of the imminent return of their fertility and of the contraceptive methods available on the day of abortion. Many women find contraceptive counseling in the abortion setting acceptable: In a large, populationbased study of 211,215 women receiving surgical and medical abortion in the United Kingdom, 85% of women accepted contraceptive counseling, which followed a shared decision-making approach, and most of these women then chose to receive a method of contraception from the clinic [18]. In the general population, high-quality interpersonal communication may influence uptake of highly effective contraceptives and continuation of those methods at 6 months [19,20].…”
Section: How Should Contraceptive Counseling Be Performed At the Timementioning
confidence: 99%
“…Thirty-five studies were included in the review and are summarised in S3 Table. Studies were published from 2001 to 2019, with 12 published in the last five years [20,[26][27][28][29][30][31][32][33][34][35][36]. Sixteen studies were cross-sectional quantitative [20,26,[29][30][31][35][36][37][38][39][40][41][42][43][44][45], 13 were cross-sectional qualitative [27,33,34,[46][47][48][49][50][51][52][53][54][55], four were mixed method [56][57][58][59], and two were quantitative cohort studies [28,32]. The study data covered eight countries (Australia, Israel, Netherlands, New Zealand, Portugal, Sweden, UK and the United States...…”
Section: Resultsmentioning
confidence: 99%
“…Initiating contraception on the day of abortion, in particular LARC, has proven significant in the reduction of subsequent abortions [2,26]. A study by Aiken et al reported that 85% of women undergoing a termination of pregnancy from BPAS clinics in England and Wales accepted contraceptive counselling; 51% chose to obtain their method from the same provider, 33% indicated a preference to obtain their contraception from their GP or a family planning clinic, 7% did not need contraception for a range of reasons and 8% declined counselling or contraception [27]. Other studies exploring women’s desires for contraceptive counselling at the time of their abortion have reported that about one-third [28] to two-thirds [29] of women were not interested in receiving counselling on the day of abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative research has highlighted the difficulties which young women may experience with their contraceptive method chosen at abortion, suggesting the need for long-term support to help managing side effects or switching to alternative contraception [30]. In addition, there is a natural delay in the immediate post-abortion contraceptive uptake of intrauterine contraceptive methods in women undergoing medical abortions where the second stage occurs at home [27]. As medical abortions constitute an increasing proportion of all induced abortions in England and Wales (62% of all induced abortions in 2016 versus 30% in 2006) [1], more women may be losing out on the opportunity for the full range of LARC methods in the absence of organised contraceptive follow-up.…”
Section: Discussionmentioning
confidence: 99%